PISA 2022: The impact of school-environment predictors on the performance of Spanish students - Pablo Javier Ortega-Rodríguez (Revista Española de Pedagogía)
The impact of school environment on academic performance has become more important over recent years. However, there are no specific studies of the impact of school environment variables on the performance of secondary school students in the PISA domains of science, reading and mathematics. This article aims to analyse the influence of a set of predictors relating to the school environment (climate, well-being, and bullying) on student performance in all three PISA domains. The sample comprises 28 781 Spanish students (14 459 male students, 50.24%; 14 322 female students, 49.76%) from 935 schools, who participated in PISA 2022. A two-level hierarchical linear model was used: students and schools. The results show that male students score higher than female students in mathematics and science, while female students score higher in reading. Male students have a more favourable opinion of school well-being than female students. Students’ economic status is a strong predictor of performance in all three PISA domains. School climate, school well-being, and bullying have more impact on performance in mathematics and science than in reading. Students in private schools perform better than those in public schools. The results of the final models explain more than 21% of the differences between students in performance in the three areas and more than 50% between schools. These findings suggest a need to create an environment that promotes student learning, reinforce students’ sense of belonging to the school, and implement anti-bullying measures in schools.